Grinding process for the production of nanofibrillated cellulose based on unbleached and bleached bamboo organosolv pulp - Correia, Viviane da Costa; Santos, Valdemir dos; Sain, Mohini; Santos, Sergio Francisco [UNESP]; Leao, Alcides Lopes [UNESP]; Savastano Junior, Holmer (Springer, 2016)
Nanofibrillated cellulose (NFC) is a type of nanomaterial based on renewable resources and produced by mechanical disintegration without chemicals. NFC is a potential reinforcing material with a high surface area and high aspect ratio, both of which increase reinforcement on the nanoscale. The raw materials used were unbleached and bleached bamboo organosolv pulp. Organosolv pulping is a cleaner process than other industrial methods (i.e. Kraft process), as it uses organic solvents during cooking and provides easy solvent recovery at the end of the process. The NFC was produced by treating unbleached and bleached bamboo organosolv pulps for 5, 10, 15 and 20 nanofibrillation cycles using the grinding method. Chemical, physical and mechanical tests were performed to determine the optimal condition for nanofibrillation. The delamination of the S2 layer of the fibers during nanofibrillation contributed to the partial removal of amorphous components (mainly lignin), which have low polarity and improved the adhesion of the fibers, particularly the unbleached cellulose. The transverse modulus of elasticity of the unbleached NFC was highest after 10 nanofibrillation cycles. Further treatment cycles decreased the modulus due to the mechanical degradation of the fibers. The unbleached NFC produced by 10 cycles have a greater transverse modulus of elasticity, the crystallite size showed increase with the nanofibrillation, and after 5 nanofibrillation cycles, no differences are observed in the morphology of the fibers.
Keywords: Nanofibrillation; Cellulose; Grinding; Reinforcement